Foundations of inclusive education research - Jones, Phyllis; Danforth, Scot (International perspectives on inclusive education ;, 2015)
This volume focuses on inquiry into inclusive education from the perspective of scholarly influences in the field of practice and research. A group of key international researchers in the field of inclusive education have each contributed a chapter about a piece of scholarship they believe has influenced inquiry in the field, as a whole.